Cost effectiveness of personal health education in primary care for people with angina in the greater Belfast area of Northern Ireland. Issue 5 (October 1996) - O'Neill, C; Normand, C; Cupples, M; McKnight, A
Abstract : STUDY OBJECTIVE: To investigate the cost effectiveness of personal health education for angina patients being treated in general practice. DESIGN: A randomised controlled trial in which people were randomised to intervention and control groups. All were assessed at the start and end of the study, with details recorded of disease status, coronary heart disease risk factors, and self assessed quality of life. A note was taken of their current use of drugs and over the course of the study their use of all health services. Those in the intervention group had three visits per year from a health visitor, whose brief was discuss ways of living more easily with their disease and in which risks of further events might be reduced. PATIENTS: Altogether 688 patents in the Greater Belfast area aged less than 75 years and known to have angina for at least six months. MAIN RESULTS: Significant improvements in survival and self assessed quality of life were found between the study and control groups. The intervention was associated with a reduction in drug usage and there was no significant difference between the intervention and control groups in terms of their use of other health services. CONCLUSION: Given the improvement in survival and self assessed quality of life and no significant differences in costs to the health service between the two groups, the intervention was deemed to be cost effective.